Internalisasi Nilai Pendidikan Agama Islam melalui Praktik Budaya Religius Sekolah di SMA Al-Izzah Batu - M. Mahbubi (Jurnal Simki Postgraduate, 2025)
This study aims to analyze the internalization of Islamic Religious Education (IRE) values through the practice of school religious culture at SMA Al-Izzah Batu. The research employs a qualitative approach with a descriptive-analytical design, focusing on understanding the process and meaning of value internalization within the school cultural context. The research subjects were selected purposively, including the principal, teachers, and students. Data were collected through observation, in-depth interviews, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that the practice of religious culture at SMA Al-Izzah Batu is systematically integrated into the school system and functions as a mechanism for internalizing Islamic Religious Education values. The internalization process occurs through habituation, modeling, and social reinforcement, which shape students’ religious behavior. However, the level of value internalization varies among students, influenced by individual internal factors. This study emphasizes that a structured and meaningful religious culture plays a significant role in developing students’ religious character and enhancing the effectiveness of Islamic Religious Education in schools.